2013
DOI: 10.1017/s1751731113001225
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism by splanchnic tissues of mature sheep fed varying levels of lucerne hay cubes

Abstract: The objective of this study was to determine the pattern of energy metabolites net flux across the portal-drained viscera (PDV) and total splanchnic tissues (TSP) in mature sheep fed varying levels of lucerne hay cubes. Four Suffolk mature sheep (61.4 6 3.6 kg BW) surgically fitted with multi-catheters were fed four levels of dry matter intake (DMI) of lucerne hay cubes ranging from 0.4-to 1.6-fold the metabolizable energy (ME) requirements for maintenance. Six sets of blood samples were simultaneously collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
(33 reference statements)
2
11
1
Order By: Relevance
“…Diet digestibility and N balance Diet digestibility has been described in detail (EL-Sabagh et al, 2013). Increasing DMI level induced linear increases in fecal and urinary N losses and N retention along with a quadratic effect of DMI on urinary total N and N balance (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diet digestibility and N balance Diet digestibility has been described in detail (EL-Sabagh et al, 2013). Increasing DMI level induced linear increases in fecal and urinary N losses and N retention along with a quadratic effect of DMI on urinary total N and N balance (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Blood and plasma flows with the basal diet are presented in detail in the companion paper (EL-Sabagh et al, 2013). Blood and plasma flows of the portal vein increased linearly (P , 0.05) with increasing DMI of the basal diet (Table 4).…”
Section: Nutrient Net Fluxmentioning
confidence: 95%
See 2 more Smart Citations
“…It is likely that the increased flow of nutrients in the tissues of animals fed with TH has favored muscle anabolism and increased the carcass weight and empty body weight of the animals (EL-Sabagh et al 2013;Riaz et al 2014). In fact, it was observed that there was a greater deposition of muscle (kg) and fat (kg) in the loin of sheep fed with FT. Means in the same row followed by different letters differ statistically (P < 0.05)…”
Section: Discussionmentioning
confidence: 99%